2001
DOI: 10.1302/0301-620x.83b1.0830118
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bone remodelling around hydroxyapatite-coated, porous-coated and grit-blasted hip replacements retrieved at post-mortem

Abstract: W e investigated the implant-bone interface around one design of femoral stem, proximally coated with either a plasma-sprayed porous coating (plain porous) or a hydroxyapatite porous coating (porous HA), or which had been grit-blasted (Interlok). Of 165 patients implanted with a Bimetric hip hemiarthroplasty (Biomet, Bridgend, UK) specimens were retrieved from 58 at post-mortem.We estimated ingrowth and attachment of bone to the surface of the implant in 21 of these, eight plain porous, seven porous HA and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 15 publications
2
64
0
2
Order By: Relevance
“…While the Alloclassic and Mayo feature gritblasted rather than porous-coated surfaces, several long-term studies of these devices have shown the identical trend of proximal bone loss and distal bone densification. Studies have also compared these two uncemented fixation techniques (when controlled for hydroxyapatite coating) and have shown no significant clinical or radiographic differences (Coathup et al, 2001;Won et al, 2004). Quantitatively, the bone mineral content had the highest levels of resorption in the proximal region and densification in mid and distal zones.…”
Section: Tablementioning
confidence: 99%
“…While the Alloclassic and Mayo feature gritblasted rather than porous-coated surfaces, several long-term studies of these devices have shown the identical trend of proximal bone loss and distal bone densification. Studies have also compared these two uncemented fixation techniques (when controlled for hydroxyapatite coating) and have shown no significant clinical or radiographic differences (Coathup et al, 2001;Won et al, 2004). Quantitatively, the bone mineral content had the highest levels of resorption in the proximal region and densification in mid and distal zones.…”
Section: Tablementioning
confidence: 99%
“…The analysis of in vivo formation of new tissue at the interfaces of bioactive implants has been reported using histological methods and the interfacial mechanical properties, such as stiffness, have also been studied [22,23]. Recently other techniques that focus at the micro-and nano-structural level analysis of the newly formed tissue, such as nanoindentation, small-angle and wide-angle X-ray scattering, Raman microscopy and elemental analysis are being used in the analysis of biological materials [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Es können diese Veränderungen aber nicht nur als Erhöhung der Stabilität der Implantate durch den raschen ossären Einheilungsprozess gedeutet werden, sondern auch auf einen raschen Verschluss des Markraums schließen lassen. Der aus den artikulierenden Oberflächen erfolgenden Partikelfreisetzung wird somit eine deutliche Barriere gegenüber dem Markraum des Femurs entgegengesetzt [14,20,29]. Schon Abb.…”
Section: Röntgen Im Axialbildunclassified
“…Dabei kann offensichtlich die Zahl der RL verringert werden [11][12][13][14][15] oder sogar ein zur zementfreien Verankerung weniger geeignetes Implantat in seinem ossären Einbau verbessert werden [16]. Tierexperimentelle Arbeiten [17][18][19] sowie auch pathologisch-histologische Untersuchungen an Humanpräparaten [20][21][22][23] zeigten das gute Anwachsverhalten des Knochens und die bessere ossäre Verankerung im Vergleich zu unbeschichteten Implantaten. Hinsichtlich der radiologischen Darstellung der Einheilung beschichteter Schäfte gibt es allerdings nur wenig Information [24][25][26].…”
unclassified